2021
DOI: 10.1093/bjsopen/zraa051
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of the SARS-CoV-2 (COVID-19) crisis on surgical training: global survey and a proposed framework for recovery

Abstract: Background The SARS-CoV-2 pandemic had a profound impact on surgical services, potentially having a detrimental impact on training opportunities. The aim of this global survey was to assess the impact of the COVID-19 crisis on surgical training and to develop a framework for recovery. Methods A cross-sectional, web-based survey was conducted. This was designed by a steering committee of medical educationalists and validated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 42 publications
1
14
1
Order By: Relevance
“…In numbers, the study by Aziz et al [2] showed that 41.3% received more didactic teaching during the pandemic than in prior years. Additionally, studies also showed that webinars, online discussions, educational videos and simulations were popular among early career doctors in multiple specialties [6,7,9,13,27].…”
Section: Discussionmentioning
confidence: 99%
“…In numbers, the study by Aziz et al [2] showed that 41.3% received more didactic teaching during the pandemic than in prior years. Additionally, studies also showed that webinars, online discussions, educational videos and simulations were popular among early career doctors in multiple specialties [6,7,9,13,27].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, technical aspects of joining remotely can be challenging. 7 With a more diverse audience from around the world, conference organizers must also consider a wide range of time differences when planning sessions.…”
Section: Virtual Conferencesmentioning
confidence: 99%
“…In 2020, an international survey-based study, including 15 specialities and 34 countries, assessed the global impact of the COVID-19 pandemic on surgical training ( 9 ), demonstrating a severe impact on all of its aspects. Interestingly, trainees from Europe reported worse consequences than those from Asia and Australia.…”
Section: Introductionmentioning
confidence: 99%